PREPARASI, MODIFIKASI DAN KARAKTERISASI KATALIS NI-MO/ZEOLIT ALAM DAN MO-NI/ZEOLIT ALAM - Wega Trisunaryanti; Endang Triwahyuni; Sri Sudiono (Faculty of Industrial Technology Universitas Islam Indonesia, 2005)
Preparations and modifications of Ni-Mo/natural zeolite and Mo-Ni/natural zeolite catalysts as well as their characterizations had been carried out. The preparations of catalysts were carried out by reacting a natural zeolite produced in Wonosari with the precursor of Ni(NO3)2.9H2O and Mo(NH4)7.6H2O. The modifications were performed by varying the rasio of Ni/Mo whereas the Mo was previously loaded to the zeolite or Mo/Ni ratio whereas the Ni was previously loaded and the total metal content was 1 wt.% based on the zeolite. The aim of this research for the fututure is to prepare catalysts with high acidity and crystallinity for the conversion of waste plastics fraction to gasoline fraction (C5-C12 hydrocarbons). The characterization of catalysts included determination of metal content using Atomic Adsorption Analysis (AAS), acidity by adsorption of ammonia or pyridine vapour base method, and crystallinity by X-ray Diffraction (XRD). The treatment of catalysts using Etilene Diamine Tetra Acetic acid (EDTA) was performed to study the metal distribution on the outer or inner surface of the zeolite. The characterization results showed that the loading of Ni and Mo to the zeolite produced higher acidity catalysts than those of monometal loaded catalysts. The increase of Ni loaded caused the decrease of catalysts acidity, on the other hand, the increase of Mo loaded caused the increase of catalysts acidity. The metals loaded on the zeolite were distributed inside the pore and at outer surface of the zeolite. For all catalyst samples, the acidities determined using ammonia were higher than those of pyridine, and the acidities determined before the EDTA treatment was lower than those after the treatment. The metals loading on the zeolite did not defect its crystallnity. Metal contents of the zeolite before the EDTA treatment were higher than those after the treatment. The relationship between the metal ratios towards the catalyst acidity was varying. The EDTA treatment to the zeolite sample enhanced the crystallinity of the sampel. Catalyst samples produced in this research have high acidities and crystallinities, thus promisingly can be used for conversion process of waste plastics to gasoline fraction. Keywords : natural zeolite, acidity, Ni-Mo/natural zeolite, Mo-Ni/natural zeolite, crystallinity, EDTA